Comparison Analysis of Business Feasibility Study between Rombong Type Coffee Business and Cafe Type Coffee Business - Prasetyo, Agung; Irma, Irma (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This research aims to analyze the feasibility of financial processing of café-type coffee business and rombong type coffee business in its financial aspects by using feasibility studies. The data retrieval method used is a method of in-person interview with coffee business owners i.e., financial statements or secondary data. The results showed that the financial processing of the rombong type coffee business namely Street Coffee Sangatta with an initial investment of Rp.187,731,940 is said to be feasible and the café-type coffee business de’ atake Cafe is also feasible with an initial investment of Rp.889,727,840 which is valued from the aspects of Net Present Value, Break Event Point, Profitability index and Payback Period. Proven by the results of this research analysis rombong type coffee shop or street coffee is very good obtained the results of Break Even Point analysis obtained 9,923 cups, Net Present Value is 224,287,823, Payback Period is 2 years 1 month, and Profitability Index is 2.2. And café type coffee shop or de’atake café is very good obtained the results of Break Even Point analysis obtained 23,855 cups, Net Present Value is 18,311,840, Payback Period is 3 years 1 month, and Profitability Index is 1.0. From these results de’atake is very much said to be worthy. The implications of the results of the study are expected as input materials and recommendations for café-type coffee business owners and rombong type coffee businesses and as reference materials for future researchers.